Pengaruh Permainan Lempar Tangkap Bola Terhadap Koordinasi Mata dan Tangan Anak Kelompok B TK Anggrek Palembang Tahun 2021 - Prima, Deli; Fauzi, Muhammad; Imtihana, Aida (EDUKASIA Jurnal Pendidikan dan Pembelajaran, 2023)
This study discusses "The Effect of Catching the Ball Game on the Eye and Hand Coordination of Children in Group B of Palembang Orchid Kindergarten in 2021". This study aims to determine how the level of eye and hand coordination of group B children before and after playing the game of throwing and catching the ball at the Palembang Anggrek Kindergarten. This type of research is quantitative experimental with One Group Pretest-Postest design (one group of subjects). The research sample consisted of 20 children consisting of 10 boys and 10 girls. Data collection techniques in this study used initial observation before being treated with throwing and catching the ball learning, observation was used to collect data at the time of treatment, a test in the form of scores was carried out to determine the results after being given treatment and documentation in the form of photos. The data analysis technique used in this study used normality test, homogeneity test and hypothesis testing. From the results of research that has been carried out to prove the hypothesis, it is obtained that is 5.566 while dk = 20 + 20 - 2 = 38 with a 5% significance level so that ttable = 2.048 is obtained because tcount = 5.566 > ttable = 2,048 then the conclusion is Ho is rejected, meaning that there is a throwing effect. Catch the ball on the eye and hand coordination of group B children at the Palembang Orchid Kindergarten in 2021.